Simultaneous determination of tartaric acid and potassium in wines using a multicommuted flow system with dialysis - Oliveira, Sara M. (2011)
A multicommuted flow system with the propulsion device placed before detection is proposed for the determination of tartaric acid and free potassium in table and Port wines. A dialysis unit was introduced to increase sample dilution and minimize matrix interferences. The determination of tartaric acid was based on the spectrophotometric monitorization of the complex formed by the dialyzed analyte with vanadate. Potentiometric measurement of potassium was carried out through an ion selective tubular electrode. Dynamic linear ranges of 0.500–5.00 g L−1 and 390–2000mgL−1 were achieved for tartaric acid and potassium determinations, respectively. Detection and quantification limits of 0.1 and 0.4 g L−1 of tartaric acid were obtained, respectively. For the potentiometric determination, a detection limit of 1×10−4 mol L−1 was achieved. The accuracy of the method was assessed by analysis of 30 wine samples by the proposed methodology and manual procedures. There were no statistical differences between the 2 sets of results, in both determinations. Relative standard deviations lower than 2.1 and 2.4% were attained by the spectrophotometric and potentiometric measurements, respectively. A determination rate of 52 h−1 was achieved.